PERANCANGAN MEDIAPROMOSI CAFÃ BLACKBIRD SEBAGAI UPAYA MENINGKATKAN BRAND LOYALTY - Putra, Hernandi Sukmana; Karsam, Karsam; Riyanto, Darwin Yuwono (Jurnal Art Nouveau, 2015)
Abstract:Blackbird CafÃ© is a business engaged in the Surabayaâs culinary and have great potential. Blackbird CafÃ© has a distinctive feel of classic retro interior feels more real and is surrounded retro stuff around the interior of CafÃ© Blackbird. With the potential of Blackbird CafÃ©, businesses in the culinary field is still lacking in terms of promoting their products. Promotional activities are essential to market a product / brand, so the brand is still remembered and can do approach to customers through promotional activities. Promotional activities by Blackbird CafÃ© is sorely lacking until now, the promotion activities only via social media and websites without any merchandise cause less attention from consument and made characteristic of Blackbird CafÃ© has not been seen in any media campaign. The problem is, altough the profit of Blackbird Cafe is quite large, it still canât compete with the cafÃ© around the environment, it caused decrease in visitors may occur due to lack of promotional activities from Blackbird CafÃ© and the lack of innovation in the promotion programs as well as many culinary business that have sprung up in Surabaya do customer approach through media promotion and merchandise. Therefore, it takes some effort to maintain customer loyalty, which one is create appropriate media campaign can enhance brand loyalty Blackbird CafÃ©.Â Keywords:Design, Media promotion, Brand Loyalty